Pendampingan Penyusunan Laporan Keuangan Berdasarkan PSAK ETAP di BUMNag Baringin Saiyo Kecamatan Lima Kaum - Nita Fitria; Sri Adella Fitri; Mega Rahmi; Nasfizar Guspendri; Khairul Marlin (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Financial reports can have a positive impact on the development of BUMNag. From financial reports, systematic data and information can be obtained on the business so as to assist in making decisions. The presentation of financial statements must be good and in accordance with the criteria that are understandable, relevant, reliable, and comparable, so that it can be useful in making decisions that affect the performance and image of the company going forward. In making financial statements, a company must comply with existing Financial Accounting Standards. In compiling the financial statements of BUMNag Baringin Saiyo encountered several obstacles, namely the problem of existing human resources, a lack of knowledge of accounting knowledge which was not sufficient to make account adjustments, and the preparation of financial statements in accordance with Financial Accounting Standards. The purpose of the service activity is to prepare financial reports for BUMNag Baringin SAIYO according to Financial Accounting Standards. The resulting financial statements consist of a Profit and Loss report, a Statement of Financial Position, and notes to the financial statements.